Woman in a Man's Pulpit: Incarnating Feminism in a Black and White Collar - Lyter Bright, Laurie (Feminist theology, 2018)
This article explores the potential applications of feminist pedagogy to the lived experience of weekly preaching from the perspective of a young, white, cis female, heterosexual faith community leader. When privilege is both obvious (whiteness, heterosexual, cis gender, middle class), but authority is simultaneously presumed and challenged based on historical constructs of theological role and presentation of gender, the act of preaching becomes a site of resistance. This article then discusses the act of homiletics - the art of interpretive storytelling, history teaching, persuasive speech, and spiritual performance - as informed by a feminist perspective. Does the pulpit present a bridge or barrier where gender is concerned? The physical act of preaching can represent an in-moment incarnating of a role, a historical step in a long-flowing river, and a psychological break point of self-erasure. This article posits that a thoughtful application of feminist pedagogy might dismantle these unspoken rules of the trade and create an opportunity for preaching as an act of resistance.